Penilaian Kinerja Pegawai Honorer Balai Pengelola Kereta Api Ringan Sumatera Selatan (BPKARSS) - Farhan Fadlu Rahman, Muhammad; Purwani, Fenny; Ipandy, Ahkmad (Universitas Multi Data Palembang, 2024)
Balai Pengelola Kereta Api Ringan Sumatera Selatan (BPKARSS) underwent restructuring in accordance with the regulations of the Ministry of Transportation. Employee performance assessment still relies on manual and subjective methods, leading to various issues. This study proposes a Decision Support System (DSS) utilizing the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method to enhance objectivity and efficiency in performance evaluations. A descriptive approach is employed to identify objectives and analyze the DSS system requirements. DSS implementation focuses on automated development using TOPSIS, improving assessment accuracy, offering performance improvement recommendations, and enhancing practical skills. The anticipated results aim to positively contribute to employee appointment decisions, enhance assessment efficiency, and fortify the performance evaluation foundation. Consequently, the adoption of DSS at BPKARSS is expected to support human resource management, stimulate career development, and elevate overall organizational performance.